Nivel de conocimientos financieros de los trabajadores de la Institución Sub CAFAE se Iquitos Maynas Loreto periodo 2022 - Chota Torres, Grecia Milagros (2024)
The present research study entitled “Financial Knowledge of the Workers of the Institution Sub Cafae SE Iquitos Maynas Loreto Period 2022”, was developed with the objective of determining the level of Financial Knowledge of the workers of the Institution Sub Cafae SE Iquitos Maynas Loreto, so it was allowed to carry out a descriptive research, with the design being non-experimental, for which there was a study population of 45 workers of the Institution who voluntarily decided to participate in this research work, and these were who answered the questions of the questionnaire designed for this purpose; Having carried out the analysis of the responses, it was determined that 100% of the workers have a medium level of financial knowledge and 86% of the workers have a high level of knowledge of Financial Instruments and 14% have a low level of knowledge of Financial Instruments, it was concluded that the workers of the Institution Sub Cafae SE Iquitos Maynas Loreto period 2022 have a medium level of financial knowledge.